Reforming the Prosecutor's Role in the Constitutional System - Rian Saputra; Nilam Firmandayu (Jurnal Justice Dialectical, 2024)
Legal uncertainty regarding the independence of the prosecutor is caused by its position as part of the executive institution, but also has a function as a judicial institution. This research is a normative legal study that employs a statutory approach to assess the suitability of regulating the prosecutor's office, whether it operates as a standalone judicial institution or as a component of an executive institution. The legal materials used are primary and secondary. The data collection technique was carried out by literature study and then analyzed using the syllogism method. The research results show, first, that regulations still overlap because the prosecutor's office carries out a judicial function, but in other interpretations, it is still under executive power. Second, a model for reforming the prosecutor's office position based on the theory of separation and distribution of power is needed to guarantee its independence in the law enforcement process. Therefore, this research can help the Indonesian government clarify the prosecutor's office's authority as a manifestation of the independent division of power.